Sistem Informasi Pendaftaran Siswa Baru Pada Sekolah SMK N 5 Bengkulu Utara Menggunakan PHP Dan MySQL - Endah Puspaningrum; Asnawati Asnawati; Achmad Fikri Sallaby (UNIVED Press, 2025)
New student registration is a crucial process in the world of education, especially in Vocational High Schools (SMK). At SMK Negeri 5 Bengkulu Utara, this process is still done manually, causing various obstacles such as delays, inefficiencies, and the risk of data input errors. To overcome these problems, a web-based new student registration information system using PHP and MySQL was developed. This research uses a descriptive method with data collection stages through interviews, and software development through structured analysis and design. The result of this research is a PPDB (New Student Admission) website that is responsive, easy to use, and equipped with features such as online registration form, document upload, admin login, applicant dashboard, announcement of selection results, and print proof of registration. This system is proven to be able to increase efficiency, accuracy, and transparency in the registration process, and make it easier for schools to manage prospective student data.